Analisa Bioktif dan Pemanfaatan Bawang Tiwai (Eleutherine Americana. Merr) Untuk Bahan Tambahan Pangan - Suroto HS (Jurnal Riset Teknologi Industri, 2016)
Food additives that are used at the moment are made of synthetyic compounds. The function of those food additives is for anticaking agent, acidity regulator, artificial sweetener, bleanching agent, flour treatment agent, emulsifier, preservatives, firming agent, food colour, flavouring, and so on. Indonesia's nature has abundant natural resources that have fungtion as food additives expecially Bawang  Tiwai growing in east kalimantan. Based on research that has been conducted, Bawang Tiwai contains active compound such as preservative and antioxidant.  The result of a laboratorium scale experiment of two fungsi i.e. Candida albicans, and Aspergillusniger, and two bacteria i.e. Staphylococcus eures and Escherchie coli, antioxidant activities proved that they can kill 50 percent. However when the antitoxicity activities were treated with Arteria larvae, it can kill until  100percent.